2010
DOI: 10.1667/rr2105.1
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Radiation Therapy Can Induce a Molecular Profile for Therapeutic Targeting

Abstract: To examine the possibility of using fractionated radiation in a unique way with molecular targeted therapy, gene expression profiles of prostate carcinoma cells treated with 10 Gy radiation administered either as a single dose or as fractions of 2 Gy × 5 and 1 Gy × 10 were examined by microarray analysis. Compared to the single dose, the fractionated irradiation resulted in significant increases in differentially expressed genes in both cell lines, with more robust changes in PC3 cells than in DU145 cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 41 publications
5
60
1
Order By: Relevance
“…These results were recently confirmed for breast, glioma, and prostate cancer cell lines (18,19) and indicate that ionizing radiation leads to the induction of the IFN/Stat1 pathway in tumor cells. STAT1 seems to have a dominant role in the expression of IRDS genes.…”
Section: Clinical-translational Advancesmentioning
confidence: 57%
“…These results were recently confirmed for breast, glioma, and prostate cancer cell lines (18,19) and indicate that ionizing radiation leads to the induction of the IFN/Stat1 pathway in tumor cells. STAT1 seems to have a dominant role in the expression of IRDS genes.…”
Section: Clinical-translational Advancesmentioning
confidence: 57%
“…Previous studies from our group demonstrated that the PC3 prostate carcinoma cell line showed a significant upregulation of immune-related genes after multifractionated treatment (12), suggesting that radiation therapy has the potential to elicit an immune response that will initiate a cascade of events leading to immunogenic antitumor effects. Corroborating evidence based on gene expression studies in prostate and breast cancers exhibited a distinctive upregulation of interferon-related genes after multifractionated therapy when compared to single-dose treatment (13).…”
Section: Introductionmentioning
confidence: 96%
“…innate immunity | cytoplasmic sensor | interferon beta | DHX58 S everal studies have shown that the response of tumor cells to ionizing radiation (IR) is associated with IFN-mediated signaling (1)(2)(3)(4)(5)(6). IFN signaling leads to the induction of multiple IFN stimulated genes (ISGs) (7,8) and activates growth arrest and cell death in exposed cell populations (9).…”
mentioning
confidence: 99%